English Advertising Slogans` Linguistic Characteristics - Anvar, Yokubov (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
Since humans are the only creatures who socialize through language and are unable to live alone, language is the most important factor that has to do with human beings, especially people. People always seek to interact with others. Thus, in order to maintain a healthy balance in life, it is imperative that people engage with others. When forming relationships, people need to communicate through language. It is capable of understanding the language's definition.